2022
DOI: 10.1111/nicc.12838
|View full text |Cite
|
Sign up to set email alerts
|

Staff knowledge, attitudes and practices regarding glycaemic management in adult intensive care units: A national survey

Abstract: BackgroundHyperglycaemia is common in critically ill adult patients. Many studies have identified the content, methods, and effects of glycaemic control but have not explored the effects of knowledge, attitudes, and practices (KAP) on glycaemic control in critically ill adults. Various factors also influence the KAP of intensive care unit (ICU) staff.AimsTo assess KAP regarding glucose management for critically ill adults among nurses and medical professionals and identify the factors that influence their KAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The cross‐sectional research design was employed by 13 studies. Of these, six originated from China to examine the knowledge, attitude, and practice regarding glycaemic control among ICU professionals, 11 to explore the relationship between alarm fatigue and burnout among critical care nurses, 12 to examine the association between shift work schedules, compensatory sleep, work–family conflict, and fatigue of shift‐working nurses, 13 to investigate stakeholders' values and preferences regarding draft recommendations for adapted physical restraint guidelines, 14 to investigate the knowledge, attitudes, and practice of prone positioning of patients among ICU nurses working in COVID19 units, 15 and to analyse the reliability and validity of a competency evaluation model for front‐line nursing staff during the outbreak of major infectious diseases 16 . From Turkey, one study 17 identified the skin problems related to using personal protective equipment by ICU nurses, and another study 18 examined the relationship between alarm fatigue and the tendency to make medical errors among ICU nurses.…”
mentioning
confidence: 99%
“…The cross‐sectional research design was employed by 13 studies. Of these, six originated from China to examine the knowledge, attitude, and practice regarding glycaemic control among ICU professionals, 11 to explore the relationship between alarm fatigue and burnout among critical care nurses, 12 to examine the association between shift work schedules, compensatory sleep, work–family conflict, and fatigue of shift‐working nurses, 13 to investigate stakeholders' values and preferences regarding draft recommendations for adapted physical restraint guidelines, 14 to investigate the knowledge, attitudes, and practice of prone positioning of patients among ICU nurses working in COVID19 units, 15 and to analyse the reliability and validity of a competency evaluation model for front‐line nursing staff during the outbreak of major infectious diseases 16 . From Turkey, one study 17 identified the skin problems related to using personal protective equipment by ICU nurses, and another study 18 examined the relationship between alarm fatigue and the tendency to make medical errors among ICU nurses.…”
mentioning
confidence: 99%